Response of sea fans to infection with Aspergillus sp. (Fungi) - Smith, G. W. (1998)
Mass mortalities of sea fans (Gorgonia spp.) off the South and Central American coasts were reported in the 1980s. In some cases, populations never recovered. Widespread tissue mortality in G. ventalina and G. flabellum throughout the Caribbean was reported in 1997. Although colony mortality was apparently lower in the more recent epizootic, the geographic distribution of the disease appeared much greater. Tissue samples of affected colonies were found to be infected with a fungus (Aspergillus sp.) with was shown to be able to cause the disease in healthy sea fans. We describe observations on the early infection process and subsequent development of the disease. Based on these observations, we report the response of Gorgina spp. to infection by Aspergillus.